Isothermal amplification for detection of Plum pox virus - Olmos, Antonio; Bertolini, Edson; Cambra, Mariano (2017)
A nucleic acid sequence-based amplification method coupled with flow-through hybridisation (NASBA-FH) was developed for Plum pox virus (PPV) detection. The detection limit of the NASBA-FH was established at two copies of control transcripts, resulting 10 times higher than that obtained by Co-PCR and 1000 times higher than the sensitivity afforded by RT-PCR. In addition, samples from 253 stone-fruit trees were collected during winter and analysed. The samples were tested using methods recommended by the European and Mediterranean Plant Protection Organization to detect PPV (DASI-ELISA, RT-PCR and Co-PCR) and by NASBA-FH. PPV diagnosis by ELISA and NASBA-FH coincided in 90.5%, while ELISA and PCR-based methods coincided in the diagnosis of 91.3% of the trees and PCR-based methods with NASBA-FH agreed in 95.2%. Results support that NASBA-FH is a suitable molecular method for routine PPV detection in the winter period.